Biomimetic Redox-Flow Battery without Traditional Electrodes (Global Journals of Research in Engineering, 2023)
Starting from Galvani bioelectrochemistry is dealing mainly with voltage generated by ion transport through ion-selective biological membranes Contrary to this starting from Volta the voltage generated in electrochemical cells is based on electron transport and redox reactions on two electrodes separated by an ion-conducting electrolyte Here we combine these ideas and present the first battery where a metal foil is acting as an electron-selective membrane Without traditional electrodes this biomimetic battery in a flow-through modification has several obvious advantages including several times smaller weight size and cost It will also be more environmentally benign than existing vanadium-based redox-flow batteries